Influence of Mixing Time and Mass Ratio of Precursor on Preparation of Magnetic Biochar Derived from Cassava Peel (Manihot utilissima) - Argo Khoirul Anas; Rosyida Mutiara; Muhammad Miqdam Musawwa; Agus Taftazani (EKSAKTA: Journal of Sciences and Data Analysis, 2022)
The use of magnetic biochar to overcome aquatic environmental problem has received interesting attention in recent years. Several methods in preparing magnetic biochar have been applied including impregnation-pyrolysis, chemical co-precipitation, and reductive co-precipitation. In case of co-precipitation method, the obtained magnetic biochar is relatively stable and easy to handle, that make it important to study. The purpose of this work is to study the influence of mixing time and mass ratio of precursor on preparation of magnetic biochar using this method. The cassava peel (Manihot utilissima) was used as feedstock for biochar preparation. The magnetic biochar which is characterised using FTIR, XRD, and SEM-EDX analysis was successfully prepared and applied as an adsorbent for MB. The optimum mixing time of precursor was identified at 60 minutes and maximum mass ratio was achieved at 1:1 of biochar:Fe3O4. Importantly, it can be known that MB adsorption successfully improved with the increase of mixing time, up to the optimum adsorption capacity at 60 minutes of precursor mixing time. Furthermore, at the mass ratio of 1:1 magnetic biochar displayed the highest adsorption capacity. The parameter in preparation method developed in this work can be used as an additional information in the magnetic biochar preparation